Case report: Rare case of a preoperatively diagnosed spermatic cord paraganglioma and literature review - Hao, Yining; Li, Xiuci; Xie, Jing; He, Wei; Wang, Chenghe; Sun, Fukang (Frontiers in Oncology, 2024)
Paraganglioma (PGL) is rare, and PGL that arises from the urogenital system is even rarer.Here, we report a case of PGL in spermatic cord and review the relevant literatures. We encountered a 15-year-old boy with a history of hypertension for almost 2 years, accompanied with headache and palpitations. His serum and urine catecholamines were elevated, but no adrenal lesions were detected, suggesting the existence of PGL. Physical examination found a painless nodule adherent to the spermatic cord in the right scrotum. A systemic Ga 68 DOTATATE PET-CT was then performed and it revealed a mass with high DOTATATE uptake in the right scrotum. The CT, MRI and ultrasound images showed the abundant blood supply to the tumor. Based on above imaging and biochemical information, a diagnosis of PGL was made prior to surgery. After 2 weeks of preparation with Cardura, an open surgery was performed to remove the tumor together with the right testis and right epididymis. Blood pressure increased to 180/100 mmHg when the tumor was touched intraoperatively, and decreased to 90/55 mmHg after the tumor was removed. Post-operative pathology confirmed our diagnosis of PGL originating from the spermatic cord. Immunohistochemistry (IHC) staining showed SDHB (+), CgA (+), synaptophysin (+), GATA3 (+), CD56 (+), sertoli cells S-100 (+) and Ki67 (5%). Genetic testing revealed a missense mutation in the SDHA gene.Only 16 cases of spermatic cord PGL have been reported to date, although it is easy to diagnose by histology and IHC examinations, pre-operative diagnosis is quite important as it can actually reduce intraoperative complications.